2022
DOI: 10.1037/cep0000285
|View full text |Cite
|
Sign up to set email alerts
|

Stimulus-based mirror effects in associative recognition revisited.

Abstract: The mirror effect, the finding that a manipulation which increases the hit rate in recognition tests also decreases the false alarm rate, is held to be a regularity of memory. Neath et al. (in press) took advantage of the recent increase in the number of linguistic databases to create sets of stimuli that differed on one dimension but were more fully equated on other dimensions known to affect memory. Using these highly controlled stimulus sets, no mirror effects were observed; in contrast, using stimulus sets… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…Similarly, MacMillan et al (2021) observed differences in d a when manipulating age of acquisition it item recognition. MacMillan et al (2022) found differences in concreteness using associative recognition. Studies using highly controlled stimuli with immediate serial recall tests have observed effects of frequency (Neath & Surprenant, 2019), concreteness (Neath & Surprenant, 2020), neighborhood size (Guitard et al, 2018), and visual similarity (Chubala et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, MacMillan et al (2021) observed differences in d a when manipulating age of acquisition it item recognition. MacMillan et al (2022) found differences in concreteness using associative recognition. Studies using highly controlled stimuli with immediate serial recall tests have observed effects of frequency (Neath & Surprenant, 2019), concreteness (Neath & Surprenant, 2020), neighborhood size (Guitard et al, 2018), and visual similarity (Chubala et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…As a second example, there is a high-frequency advantage on serial recall tests with standard forward recall but no effect of frequency with backward recall (Hulme et al, 1997). As a third example, there is a low-frequency advantage on item recognition tests (Gorman, 1961; Schulman, 1967), but the most common result on associative recognition tests is a high-frequency advantage (Aue et al, 2018), although a number of studies report no effect of frequency (Hockley, 1994; MacMillan et al, 2022). As a final example, there is no effect of frequency on serial recognition tests (Chubala et al, 2019).…”
mentioning
confidence: 99%
“…This pattern of variability stands in stark contrast to other manipulations. For example, when memory for concrete and abstract words is examined, there is a concreteness advantage for free recall (Paivio & Csapo, 1969), for both forward and backward serial recall (Walker & Hulme, 1999), for both item (Gorman, 1961; Neath et al, 2021) and associative recognition (MacMillan et al, 2022), and also for serial recognition (Chubala et al, 2019).…”
mentioning
confidence: 99%